The alarmin S100A12 causes sterile inflammation of the human chorioamniotic membranes as well as preterm birth and neonatal mortality in mice. Issue 6 (11th October 2021) - Motomura, Kenichiro; Romero, Roberto; Plazyo, Olesya; Garcia-Flores, Valeria; Gershater, Meyer; Galaz, Jose; Miller, Derek; Gomez-Lopez, Nardhy
Abstract: Sterile inflammation is triggered by danger signals, or alarmins, released upon cellular stress or necrosis. Sterile inflammation occurring in the amniotic cavity (i.e. sterile intra-amniotic inflammation) is frequently observed in women with spontaneous preterm labor resulting in preterm birth, the leading cause of neonatal morbidity and mortality worldwide; this condition is associated with increased amniotic fluid concentrations of alarmins. However, the mechanisms whereby alarmins induce sterile intra-amniotic inflammation are still under investigation. Herein, we investigated the mechanisms whereby the alarmin S100A12 induces inflammation of the human chorioamniotic membranes in vitro and used a mouse model to establish a causal link between this alarmin and adverse perinatal outcomes. We report that S100A12 initiates sterile inflammation in the chorioamniotic membranes by upregulating the expression of inflammatory mediators such as pro-inflammatory cytokines and pattern recognition receptors. Importantly, S100A12 induced the priming and activation of inflammasomes, resulting in caspase-1 cleavage and the subsequent release of mature IL-1β by the chorioamniotic membranes. This alarmin also caused the activation of the chorioamniotic membranes by promoting MMP-2 activity and collagen degradation. Lastly, the ultrasound-guided intra-amniotic injection of S100A12 at specific concentrations observed in the majority of women with sterile intra-amniotic inflammation induced preterm birth (rates: 17% at 200 ng/sac; 25% at 300 ng/sac; 25% at 400 ng/sac) and neonatal mortality (rates: 22% at 200 ng/sac; 44% at 300 ng/sac; 31% at 400 ng/sac), thus demonstrating a causal link between this alarmin and adverse perinatal outcomes. Collectively, our findings shed light on the inflammatory responses driven by alarmins in the chorioamniotic membranes, providing insight into the immune mechanisms leading to preterm birth in women with sterile intra-amniotic inflammation. Abstract : The alarmin S100A12 induces an inflammasome-mediated inflammatory response in the human chorioamniotic membranes and can cause preterm birth and neonatal mortality in mice.